Iowa CBC reporting form, Spirit Lake, December 21, 1985 - Harr, Douglas C.et al (1985)
Checklist dated December 21, 1985 compiled by Douglas Harr. A list of birds sighted by Harr and fifteen others around Spirit Lake. A total of 38 species and 7,894 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed